Farmers Adaptation as Local Wisdom in Drought Disaster in Simpenan Sub-District, Sukabumi District - Muhammad Zakaria; Danu Priyono; Ruby Dwijayanti (UNIVED Press, Dehasen University Bengkulu, 2023)
The farmer community is never separated from drought as an environmental cycle. This study aims to determine the adaptation formed by the environment of hydrometeorological disasters as the most important factor in shaping local wisdom in shaping the adaptation of farmers to the climate. This study uses data triangulation to clarify the differences and similarities of in-depth information and the adaptation process. In this study, found the stages of adaptation in drought resilience. The findings of this study are that repeated disasters will form a pattern of adaptation. The results obtained from the adaptation pattern resulting from interactions with the environment.